The Neurotropic Parasite Toxoplasma gondii Induces Astrocyte Polarization Through NFκB Pathway - Jin, Yu; Yao, Yong; El-Ashram, Saeed; Tian, Jiaming; Shen, Jilong; Ji, Yongsheng (Frontiers in Medicine, 2019)
Background Toxoplasma gondii is a protozoan parasite that chronically infects nearly one-third of the world's human population. In immunosuppressed individuals and fetus, infection of T. gondii contributes to a series of devastating conditions, including toxoplasmic encephalitis (TE), which is characterized by neuron damage in central nervous system (CNS).Astrocyte polarization is currently found in some neurodegenerative diseases, and A1 subtype of astrocyte leads to neuron apoptosis. However, little information has been available on the role of astrocyte polarization in TE. Methods In the present study, we established a mouse model to study toxoplasmic encephalitis and detected A1 astrocyte in the brains of mice with TE. Expression level of A1 astrocyte-specific marker C3 was evaluated using indirect fluorescent assay (IFA) and Western Blotting. Primary mouse astrocytes were incubated with different concentrations of T. gondii excreted-secreted antigens (TgESAs) in vitro. Expression level of C3 and A1 astrocyte-specific transcription levels were assessed using Western Blotting and qRT-PCR respectively. Bay11-7082 was used to study NFB pathway in TgESAs-induced astrocyte polarization. Results In mice with TE, the proportion of A1 astrocyte (GFAP + C3 + ) increased significantly. The results of in vitro study showed thatTgESAs induced astrocyte polarization to A1 subtype. Blocking of NFB pathway by Bay11-7082 inhibited TgESA-induced astrocyte polarization. Conclusions Our preliminary study showed the involvement of A1 astrocyte in the process of TE in mice, and TgESAs could trigger astrocyte to polarize to A1 subtype. These findings suggest a new mechanism underlying the neuropathogenesis induced by T. gondii infection.